Novel Coordination Compounds of Pterin Ligands Including a Redox Amphoteric W(IV)-pterin Complex: The Redox Chemistry Associated with their Formation and Reactivities - Samir Sen; Siddhartha S. Baisya; Parag S. Roy (Progress in Chemical Science Research Vol. 8, 2023)
The ability of the pyrazine moiety (of the pterin ring) to exist in three different oxidation states, such as the aromatic, dihydro, and tetrahydro forms, is closely related to the ability of pterins to act as redox partners in biological redox systems. High bioavailability and unique chemical versatility are the principal reasons for the incorporation of Mo and W into the active sites of enzymes. The lower reduction potentials of the tungsten complexes as compared to the corresponding molybdenum complexes, made them useful to the early life forms which probably arose in hot, anaerobic conditions of primordial ocean. The redox chemistry associated with the formation and reactivities of the title complexes, is relevant to the functional aspects of Mo/W – dependent oxotransferases.